2014
DOI: 10.1016/j.juro.2013.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2012 American Urological Association Vasectomy Guidelines on Post-Vasectomy Outcomes

Abstract: Purpose The 2012 American Urological Association (AUA) vasectomy guidelines recommend the finding of rare nonmotile sperm, representing 100,000 or fewer nonmotile sperm per ml, as a metric of post-vasectomy success. At our institution success was previously defined as 2 sequential azoospermic centrifuged semen pellets. The criteria change of including rare nonmotile sperm as a success end point may simplify post-vasectomy followup and decrease the number of post-vasectomy semen analyses required to assure occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…[11][12][13] Our original postvasectomy success rate, based solely on azoospermia, was 69%, which was lower than the estimated 76% reported in a civilian cohort. 8 After repeat analysis using the new guidelines, our postvasectomy success rate increased to 94% and was comparable with the current civilian rate of 97%, likely due to the inclusion of RNMS as success. 8 According to the 2012 AUA postvasectomy guidelines, 94.4% of our patients met the sterility criteria after 1 PVSA and 98.9% after the second PVSA.…”
Section: Comment Redefining Success and Time To Sterilitymentioning
confidence: 50%
See 3 more Smart Citations
“…[11][12][13] Our original postvasectomy success rate, based solely on azoospermia, was 69%, which was lower than the estimated 76% reported in a civilian cohort. 8 After repeat analysis using the new guidelines, our postvasectomy success rate increased to 94% and was comparable with the current civilian rate of 97%, likely due to the inclusion of RNMS as success. 8 According to the 2012 AUA postvasectomy guidelines, 94.4% of our patients met the sterility criteria after 1 PVSA and 98.9% after the second PVSA.…”
Section: Comment Redefining Success and Time To Sterilitymentioning
confidence: 50%
“…8 After repeat analysis using the new guidelines, our postvasectomy success rate increased to 94% and was comparable with the current civilian rate of 97%, likely due to the inclusion of RNMS as success. 8 According to the 2012 AUA postvasectomy guidelines, 94.4% of our patients met the sterility criteria after 1 PVSA and 98.9% after the second PVSA. The difference in success rate from 1 PVSA to the addition of a second was marginal.…”
Section: Comment Redefining Success and Time To Sterilitymentioning
confidence: 50%
See 2 more Smart Citations
“…Patient compliance with post-vasectomy semen analysis is poor. Multiple studies have suggested upwards of 50% of patients will not complete a single post-vasectomy semen analysis ( 8 , 14 - 16 ). By defining sterility as less than 100,000 non-motile sperm per milliliter, there has been a decrease in the number of repeat testing that has been performed and allows greater success rates at the first post-vasectomy semen analysis.…”
Section: Ensuring Sterilitymentioning
confidence: 99%